Academician of NAMS of Ukraine, Rector of SE «DMA of Health Ministry of Ukraine» Georgy Viktorovych Dziak is 70 - SE «Dnipropetrovsk medical academy of Health Ministry of Ukraine» (Medičnì Perspektivi)
Georgy Viktorovych Dziak